Mechanical Properties Analysis on the Reduced Graphene Oxide/Silver Nano Particle / Poly Lactic Acid Composites - Iwan Setiawan; Charlene Tiara Rehueliah Pingak; Amartya Natayu; Budi Hadisujoto; Murni Handayani (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2023)
We present the characteristics and mechanical strength of rGO-AgNPs nanocomposites in PLA-based 3D printing. The nanocomposites are characterized using X-ray diffraction and UV-Vis spectroscopy. The XRD spectrum reveals diffraction peaks at 38.14°, 44.30°, 64.50°, and 77.42°, corresponding to the (111), (200), (220), and (3111) planes of the Ag crystals, respectively. Surface observations under the microscope for pure PLA and PLA rGO-AgNPs showed that the surfaces of the samples were uniformly distributed. The results of 3D printing indicated that the 0.10 g rGO-AgNPs nanocomposite particles were evenly distributed, although digital microscopy confirmed the presence of a few small particles that were not uniformly distributed. Tensile tests demonstrated that rGO-AgNPs exhibited higher tensile strength compared to pure PLA. Tensile strength increased as the quantity of rGO-AgNPs decreased. Young's modulus results, ranging from pure PLA to rGO-AgNPs, consistently showed an increase, with the highest Young's modulus measuring 7624.45 kPa. Therefore, specimens containing rGO-AgNPs displayed a greater modulus than others, indicating that rGO-AgNPs enhanced the mechanical properties of PLA-based 3D printing.